Modeling of gas evolution processes in porous electrodes of zero-gap alkaline water electrolysis cells. (1st May 2022) - Lee, Jaeseung; Alam, Afroz; Park, Chungi; Yoon, Soobin; Ju, Hyunchul
Highlights: A three-dimensional two-phase alkaline water electrolysis model was developed. This model is using an inhomogeneous Euler–Euler mixture modeling approach. The model was successfully validated against experimentally measured I–V curves. The initiation of two-phase flow and the effect of bubble coverage were examined. The bubbles occurred at low electrolyte flow rates increased the overpotentials. Abstract: A three-dimensional two-phase model of an alkaline water electrolysis (AWE) cell containing potassium hydroxide solution was developed by meticulously considering gas evolution reactions, the dissolution of the evolved gas in the electrolyte, bubble formation above the critical oversaturation limit, blockage effects of electrochemical reactions, and charge transport by bubbles. A numerical two-phase model based on the Euler–Euler approach was adopted to describe bubbly two-phase flow during the cell's operation. The numerical model was first validated against experimental data obtained for a wide range of current densities (up to 2.0 A/cm 2 ). Subsequently, the effect of two-phase flow on the AWE performance was determined by conducting a comparative study in which various cell scales and operating conditions were considered. In particular, the initiation of two-phase flow and the effect of bubble coverage of the electrodes were examined for various electrolyte flow rates, operating current densities, and cell sizes. Simulation results showed that the nucleation of bubbles and the subsequent development of two-phase flow occurred at low electrolyte flow rates and/or for large-sized cells and that they increased the ohmic and activation overpotentials.